Attachment style and men's patterns of sports fan devotion. (September 2021) - Levental, Orr; Yaffe, Yosi; Noy, Ran; Sharabi, Uriya; Ben-Eli, Michal
Abstract: This study considers whether secure and insecure attachment styles acquired in the early stages of life are related to adults' patterns of devotion to their favorite sport team by examining these patterns after exposure to the object of devotion. In addition, the study examines whether the desire to reinforce self-esteem and the ability of those with a secure attachment style to utilize their favorite team as a source of increasing their self-esteem can explain a person's devotion patterns. The entire study was conducted online and measured participants' attachment style, self-esteem, and extent of their devotion to their team through exposure or non-exposure to the object of their devotion. The study participants included 185 men aged 18 to 49 who are fans of various football teams. According to the results, fans with a secure attachment style exhibit higher levels of self-esteem and devotion than fans with an insecure attachment style. Moreover, fans with a secure attachment style who watched a video of their team (object of devotion) were found to exhibit higher levels of devotion than fans with a secure attachment style who were not exposed to their object of devotion. On the other hand, participants with an insecure attachment style demonstrated a reverse pattern, so that fans who watched a video of their team reported lower levels of devotion than those with insecure attachment style who had not been exposed to such content. Highlights: Fans with a secure attachment style exhibited higher self-esteem and team devotion than fans with an insecure attachment style. Fans with a secure attachment style who watched a video of their team (object of devotion) exhibited higher levels of team devotion than fans with a secure attachment style who were not exposed to their object of devotion. Not only do fans with insecure attachment style exhibit lower levels of devotion, but their exposure to content related to their favorite team (object of devotion) lowers their level of interest and involvement.